(untitled) (Research, Society and Development, 2021)
The civil construction sector is increasingly expanding due to demographic growth; consequently, greater demand for housing construction. However, there has been an alarming increase in the volume of generation of solid waste from construction and demolition (RCD). Therefore, this work has as main objective to use residues generated by physical losses in construction sites for partial and total replacement of the coarse aggregate of conventional concretes and to analyze its efficiency for structural purposes. For this purpose, experimental tests were carried out with the replacement of conventional coarse aggregate for aggregate consisting of construction and demolition waste in the contents of 50% and 100%. The results obtained were compared with that of conventional concrete. The reuse of RCD in the manufacture of conventional concretes may bring sustainable management to buildings, since their use can generate a reduction in the exploitation of natural resources, a decrease in the volume of waste deposited in the environment and a reduction in the CO2 emission, generated by the operations of transport of this material to its destination. Therefore, we sought to gather data / research to present how the feasibility of making recycled concrete from construction and demolition waste helps in the search for sustainable alternatives for the deposition of this waste. With the results obtained it was possible to observe that the recyclable concretes presented satisfactory values ​​for their use in civil construction if all technological control is carried out for their production and execution and can be used for structural purposes.